Glycated hemoglobin predicts overall and cardiovascular mortality in non-diabetic hemodialysis patients - Ok, Ebru Sevinc; Asci, Gulay; Toz, Huseyin; Ritz, Eberhard; Kircelli, Fatih; Sever, Mehmet Sukru; Ozkahya, Mehmet; Sipahi, Savas; Dheir, Hamad; Bozkurt, Devrim; Omer, Ziya; Sahin, Osman Z.; et al. (Clinical nephrology, 2014)
AIMS: Besides diabetic patients, glycated hemoglobin (HbA1c) levels have been reported to predict mortality in non-diabetics patients. However, the importance of HbA1c levels in non-diabetic hemodialysis patients still remains unknown. Thus, we aimed to prospectively investigate the impact of HbA1c on all-cause and cardiovascular mortality in a large group of prevalent non-diabetic hemodialysis patients. - METHODS: HbA1c was measured quarterly in 489 non-diabetic prevalent hemodialysis patients. Overall and cardiovascular mortality were evaluated over a 3 year follow-up. - RESULTS: Mean HbA1c level was 4.88 ± 0.46% (3.5 - 6.9%). During the 28.3 ± 10.6 months follow-up period, 67 patients (13.7%) died; 31 from cardiovascular causes. In Kaplan-Meier analysis, patients in the lowest (< 4.69%) and highest HbA1c (> 5.04%) tertiles had poorer overall survival compared to the middle HbA1c tertile (p < 0.001). Adjusted Cox-regression analysis revealed that the highest HbA1c tertile was associated with both overall (HR = 3.60, 95% CI 1.57 - 8.27, p = 0.002) and cardiovascular (HR = 6.66, 95% CI 1.51 - 29.4; p = 0.01) mortality. Also, low HbA1c levels tended to be associated with overall mortality (HR = 2.26, 95% CI 0.96 - 5.29, p = 0.06). - CONCLUSION: Upper normal HbA1c levels are independently associated with cardiovascular and overall mortality in non-diabetic hemodialysis patients, whereas lower HbA1c levels are not.
Gesehen am 16.02.2021